2016
DOI: 10.1093/mnras/stw552
|View full text |Cite
|
Sign up to set email alerts
|

A novel look at energy equipartition in globular clusters

Abstract: Two-body interactions play a major role in shaping the structural and dynamical properties of globular clusters (GCs) over their long-term evolution. In particular, GCs evolve toward a state of partial energy equipartition that induces a mass-dependence in their kinematics. By using a set of Monte Carlo cluster simulations evolved in quasiisolation, we show that the stellar mass dependence of the velocity dispersion σ(m) can be described by an exponential function σ 2 ∝ exp(−m/m eq ), with the parameter m eq q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
130
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(138 citation statements)
references
References 41 publications
8
130
0
Order By: Relevance
“…In contrast, for strongly mass segregated clusters the variation of the M/L ratio can reach a factor of 4 between the core region and the cluster outskirts. This agrees with recent results of Monte Carlo simulations by Bianchini et al (2016), who found that the amount of mass segregation tightly correlates with the dynamical state of the cluster. Table 2 presents a summary of our results.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, for strongly mass segregated clusters the variation of the M/L ratio can reach a factor of 4 between the core region and the cluster outskirts. This agrees with recent results of Monte Carlo simulations by Bianchini et al (2016), who found that the amount of mass segregation tightly correlates with the dynamical state of the cluster. Table 2 presents a summary of our results.…”
Section: Resultssupporting
confidence: 92%
“…Hence the assumption of a constant mass-to-light ratio is not valid for globular clusters. In addition, due to energy equipartition, massive stars move more slowly at a given radius compared to average cluster stars (Trenti & van der Marel 2013;Bianchini et al 2016). As a result, the velocity dispersion derived from giant stars will underestimate the true velocity dispersion, which leads to an underestimation of the total cluster mass if mass segregation is not properly taken into account (Shanahan & Gieles 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that all our model clusters reach similar minimum values of δα may be due to clusters not actually being able to evolve to a state of pure energy equipartition (Merritt 1981;Miocchi 2006;Trenti & van der Marel 2013;Gieles & Zocchi 2015;Bianchini et al 2016), with the minimum δα representing the highest state of energy equipartition a star cluster can reach.…”
Section: Discussionmentioning
confidence: 90%
“…Gieles et al 2006;Kruijssen et al 2011Kruijssen et al , 2012Renaud & Gieles 2013;Rieder et al 2013), stellar evolution is the initial driver behind cluster evolution and early expansion due to mass loss from high-mass stars. After this early stage, two-body relaxation takes over and the cluster evolves towards a state of partial energy equipartition (Merritt 1981;Miocchi 2006;Trenti & van der Marel 2013;Gieles & Zocchi 2015;Bianchini et al 2016). A natural result of two-body relaxation is the segregation of higher mass stars towards the cluster center while lower mass stars migrate outwards (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, simple isotropic and nonrotating models (King 1966) are usually adopted to reproduce their observed surface brightness/star count profiles and to derive their structural parameters (e.g., Harris 1996). However, recent N-body simulations indicate that GCs do not attain complete energy equipartition (Trenti & van der Marel 2013; see also Bianchini et al 2016), and they may show differential rotation and complex behaviors of pressure anisotropy, depending on the degree of dynamical evolution suffered and the effect of an external tidal field (e.g., Vesperini et al 2014).…”
Section: Introductionmentioning
confidence: 99%